2023
DOI: 10.3389/fphar.2023.1264345
|View full text |Cite
|
Sign up to set email alerts
|

Decoding tumor heterogeneity in uveal melanoma: basement membrane genes as novel biomarkers and therapeutic targets revealed by multi-omics approaches for cancer immunotherapy

Yunyue Li,
Huabao Cai,
Jinyan Yang
et al.

Abstract: Background: Uveal melanoma (UVM) is a primary intraocular malignancy that poses a significant threat to patients’ visual function and life. The basement membrane (BM) is critical for establishing and maintaining cell polarity, adult function, embryonic and organ morphogenesis, and many other biological processes. Some basement membrane protein genes have been proven to be prognostic biomarkers for various cancers. This research aimed to develop a novel risk assessment system based on BMRGs that would serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Regarding one of the important parts of TME, extracellular matrix, Li et al have developed a prognostic model for UM based on basement membrane genes that can predict the response to immunotherapy. They also analyzed the expression patterns of these genes in different immune cells with the help of single-cell RNA sequencing (scRNA-seq) data [135]. Incidentally, High throughput gene expression analysis with bioinformatic tools paves the way for more analysis in finding different cellular patterns and expression of immunological pathways in TME that are shared by many tumors [136,137].…”
Section: Characteristic Genetic Aberrations Per Tcga Classmentioning
confidence: 99%
“…Regarding one of the important parts of TME, extracellular matrix, Li et al have developed a prognostic model for UM based on basement membrane genes that can predict the response to immunotherapy. They also analyzed the expression patterns of these genes in different immune cells with the help of single-cell RNA sequencing (scRNA-seq) data [135]. Incidentally, High throughput gene expression analysis with bioinformatic tools paves the way for more analysis in finding different cellular patterns and expression of immunological pathways in TME that are shared by many tumors [136,137].…”
Section: Characteristic Genetic Aberrations Per Tcga Classmentioning
confidence: 99%
“…Moreover, researchers had constructed a m7Grelated prognostic signature by integrating TCGA and GEO database and suggested PAG1 as biomarker for diagnosis and treatment of UM (29). Yunyue Li et al also developed a prognostic risk model based on basement membrane protein-related genes (30), and glycosylation-based gene signature and hypoxia-related gene signature were described as well by integrating single-cell analysis and machine learning (31,32). Re-analyzing publicly available single cell RNA sequencing, researchers found that FOXD1 exclusively expressed in high-risk UM and its expression is associated with a poor prognosis, suggesting FOXD1 as a new biomarker for the diagnosis of UM (33).…”
Section: Biomarkers and Predictive Modelsmentioning
confidence: 99%
“…In the study of Yunyue Li et al, ADAMTS10 and ITGA5 were expressed in various immune cell, and ITGA5 showed predominant expression in CD8 +Tex and CD8+ T immune cell populations. Further studies should be carried out to study the function of those basement membrane protein-related genes in TME and immunotherapy of UM (30). Liping Shen et al conducted a pan cancer research of NQO1 and found that NQO1 was significantly upregulated in most cancer types.…”
Section: Tme and Insight Into Immunotherapymentioning
confidence: 99%